Management challenges for the 21st century - Drucker, Peter F. (Harper Business New YorkUS, 1999)
Identifies changes in areas including: demographics, politics, society, philosophy, economics; and stresses the need for appropriate strategic planning. Examines topics such as: the tasks of the change leader and, information challenges. Advises workers to manage themselves in various areas including: their strengths, performance, learning styles, values, contribution and relationships.